Influence Leadership Transformational, Discipline Work, and Work Stress on Performance Employee on PT. Titans Agency Prudential Life Assurance in Surabaya - Sri Wahyuni; Tri Andjarwati (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This research is to find out and analyze whether Transformational Leadership has an effect on Work Stress, to find out and analyze whether Work Discipline has an effect on Work Stress, to know and analyze whether Transformational Leadership has an effect on Performance Employees, to. Design/methodology/approach: The sample data in this study were 16 respondents. Analysis which is used is Path Analysis (Path Analysis). Findings: The results of this study show that Leadership Transformational no there is influence significant to work stress at PT. Titans Agency Prudential Life Assurance, Work Discipline does not exist significant influence on Work Stress at PT Titans Agency Prudential Life Assurance, Leadership Transformational there is influence significant negative to Performance Employee on PT Titans Agency Prudential Life assurance, Discipline Work there is positive significant effect on Employee Performance at PT Titans Agency Prudential Life Assurance, Work Stress has a significant negative effect on Employee Performance at PT Titans Agency Prudential Life Assurance,. Research limitations/implications: Find out and analyze whether Work Discipline has an effect on Employee Performance, to find out and analyze whether work stress has an effect Against Employee Performance. Practical implications : This study leader PT Titans Agency Prudential Life Assurance recommended for adjusting work deadlines with stress work which given to employee. So that employee could complete which always Chase target. Originality/value: This paper is original Paper type: a Research Paper